2007
DOI: 10.1016/j.ejcnurse.2006.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Follow-Up of Self-Care Behaviour after a Single Session Education of Patients with Heart Failure in Primary Health Care

Abstract: Background: Improved self-care behaviour is a goal in educational programmes for patients with heart failure, especially in regard to daily self-weighing and salt and fluid restriction. Aims: The objectives of the present study were to: (1) describe self-care with special regard to daily self-weighing and salt and fluid restriction in patients with heart failure in primary health care, during one year of monthly telephone follow-up after a single session education, (2) to describe gender differences in regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 35 publications
3
67
2
10
Order By: Relevance
“…In contrast to our findings, Holst et al [26] found no significant changes in self-care behavior or quality of life during 1 year of monthly telephone follow-up conducted for patients with heart failure. They suggested more extensive interventions to enhance self-care behavior considering patients' cognitive function, personality, and environment.…”
Section: Wwwkanorkrcontrasting
confidence: 99%
“…In contrast to our findings, Holst et al [26] found no significant changes in self-care behavior or quality of life during 1 year of monthly telephone follow-up conducted for patients with heart failure. They suggested more extensive interventions to enhance self-care behavior considering patients' cognitive function, personality, and environment.…”
Section: Wwwkanorkrcontrasting
confidence: 99%
“…A large proportion of patients (77%) did not report their weight gain to their doctors and 50% did not consider a sudden weight gain to be important (15) . One study showed that only 46% of patients received instructions about the importance of daily weight control (16) .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the motivation and lack of knowledge about the need for weight control are also mentioned as causes of poor adherence (12,(15)(16) .…”
Section: Discussionmentioning
confidence: 99%
“…Females also display better weight control at 3-12 months. 62 Although indicated in both sexes, 63 women obtain less defibrillator and pacemaker implantations than men; 64 some authors have questioned the degree of ICD benefit in women considering that they display lower mortality on placebo. 65 Lower rates of heart transplantation in women have been attributed to higher refusal rates, a factor also influenced by lower socioeconomic status.…”
Section: Managementmentioning
confidence: 99%